2020
DOI: 10.3390/microorganisms8040468
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Derivatives as Potential Antimicrobial Agents against Staphylococcus aureus Planktonic Cells

Abstract: In this work, the antibacterial activity of deflazacort and several of its synthetic precursors was tested against a panel of bacterial pathogens responsible for most drug-resistant infections including Staphylococcus aureus, Enterococcus spp., Acinetobacter baumannii, Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, and Enterobacter spp. The derivative of deflazacort, PYED-1 (pregnadiene-11-hydroxy-16α,17α-epoxy-3,20-dione-1) showed the best antibacterial activity in a dose-dependent way. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…The transcriptional levels of isaA (immunodominant staphylococcal antigen) were also markedly (12-fold) reduced (Table 1 and Figure 3). In contrast, the transcriptional levels of isaA were increased by PYED-1 in planktonic cells [11]. Changes in the transcriptional control of isaA in planktonic cells and preformed biofilms were also observed when treating planktonic and biofilm cells with secalonic acid D [31].…”
Section: Biofilm Gene Expressionmentioning
confidence: 96%
See 4 more Smart Citations
“…The transcriptional levels of isaA (immunodominant staphylococcal antigen) were also markedly (12-fold) reduced (Table 1 and Figure 3). In contrast, the transcriptional levels of isaA were increased by PYED-1 in planktonic cells [11]. Changes in the transcriptional control of isaA in planktonic cells and preformed biofilms were also observed when treating planktonic and biofilm cells with secalonic acid D [31].…”
Section: Biofilm Gene Expressionmentioning
confidence: 96%
“…Our previous data showed that PYED-1 inhibition of S. aureus biofilm formation is associated with reduced expression of several genes involved in S. aureus virulence [11]. Here, we investigated the molecular mechanism responsible for the eradication activity of PYED-1.…”
Section: Biofilm Gene Expressionmentioning
confidence: 96%
See 3 more Smart Citations